2018
DOI: 10.35762/aer.2018.40.3.1
|View full text |Cite
|
Sign up to set email alerts
|

PM10 and PM2.5 from Haze Smog and Visibility Effect in Chiang Mai Province Thailand

Abstract: Air pollution from haze smog in Chiang Mai Thailand has become a serious problem, with fine particulate matter (FPM), PM10and PM2.5, as the main culprits. These pollutants haveserious effects on health and affect visibility in transportation and tourism. In this study, reduction in visibility was monitored using a digital camera, video records and aerial photography. Visibility in Chiang Mai was analyzed using qualitative and quantitative methods. Visibility wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Epidemiological studies have revealed a robust correlation between PM 2.5 levels and the morbidity of cardiovascular and respiratory diseases [1,2]. In addition, PM 2.5 has strong extinction abilities, and therefore, reduces atmospheric visibility and affects traffic safety [3,4]. Tropospheric ozone (O 3 ), as another air pollutant, has adverse effects on human health, ecosystems, and crop growth [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have revealed a robust correlation between PM 2.5 levels and the morbidity of cardiovascular and respiratory diseases [1,2]. In addition, PM 2.5 has strong extinction abilities, and therefore, reduces atmospheric visibility and affects traffic safety [3,4]. Tropospheric ozone (O 3 ), as another air pollutant, has adverse effects on human health, ecosystems, and crop growth [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It also varies greatly with altitude; while the visibility on Doi Inthanon or Doi Suthep can be above 10km, at the same time, Chiang Mai city centre has a visibility below 3 km. As the altitude decreases, the correlation between visibility and PM2.5 becomes stronger with R 2 >0.96 in low level basins (Pengchai et al, 2009;Jeensorn et al, 2018) (Fig. 5.10).…”
Section: Atmospheric Effects At Ground Levelmentioning
confidence: 94%
“…There are many health problems from exposure to particulate matter with a diameter of less than 10 µm (PM10). Exposure to PM10 can affect the heart and lungs, causing chronic bronchitis and emphysema [5][6]. Also, other pollutants that bound to PM10, such as PAHs, should be a concern.…”
Section: Applied Environmental Researchmentioning
confidence: 99%